2020
DOI: 10.1017/s003329172000063x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of shared genetic etiology and possible causal relations between tobacco smoking and depression

Abstract: Backgrounds Cigarette smoking is strongly associated with major depressive disorder (MDD). However, any genetic etiology of such comorbidity and causal relations is poorly understood, especially at the genome-wide level. Methods In the present in silico research, we analyzed summary data from the genome-wide association study of the Psychiatric Genetic Consortium for MDD (n = 191 005) and UK Biobank for smoking (n = 337 030) by using various biostatistical methods including Bayesian colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…MR Egger, a classic two-sample method more robust to confounding by horizontal pleiotropy, also detected no pairs in vertical pleiotropy. In contrast, the other two-sample MR analyses more susceptible to such confounding (Verbanck et al, 2018) reported multiple pairs of causal associations, similar to past findings: genetic liability to ADHD associated with increased risk of smoking initiation (Fluharty, Sallis, & Munafò, 2018) and vice versa (Treur et al, 2019), and genetic liability to smoking associated with increased risk of schizophrenia and depression and vice versa (Wootton et al, in press; Yao et al, in press); but see also some null MR findings (Gage et al, 2017; Hodgson et al, 2020; Taylor et al, 2014). Heterogeneity statistics from classic MR were significant for five out of eight associations ( p < 0.05), indicating further the potential presence of horizontal pleiotropy for these five pairs (Bowden, Hemani, & Davey Smith, 2018).…”
Section: Discussionsupporting
confidence: 72%
“…MR Egger, a classic two-sample method more robust to confounding by horizontal pleiotropy, also detected no pairs in vertical pleiotropy. In contrast, the other two-sample MR analyses more susceptible to such confounding (Verbanck et al, 2018) reported multiple pairs of causal associations, similar to past findings: genetic liability to ADHD associated with increased risk of smoking initiation (Fluharty, Sallis, & Munafò, 2018) and vice versa (Treur et al, 2019), and genetic liability to smoking associated with increased risk of schizophrenia and depression and vice versa (Wootton et al, in press; Yao et al, in press); but see also some null MR findings (Gage et al, 2017; Hodgson et al, 2020; Taylor et al, 2014). Heterogeneity statistics from classic MR were significant for five out of eight associations ( p < 0.05), indicating further the potential presence of horizontal pleiotropy for these five pairs (Bowden, Hemani, & Davey Smith, 2018).…”
Section: Discussionsupporting
confidence: 72%
“…In addition, smokers were found to have more difficulties expressing their emotions as well as identifying their feelings in comparison with the nonsmoker group [27]. Depressive symptoms as well as aggressive behaviors where more prominent in smokers [28]. Consequently, cigarette and waterpipe smoking could be associated with alexithymic behavior and this might be attributed to higher rates of depression and aggressive behaviors among smokers [27].…”
Section: Open Accessmentioning
confidence: 99%
“…Patients with depressive disorders also smoke more frequently than the general population. Several genetic studies have found that there is a correlation between smoking status and major depressive disorder (MDD) [51][52][53][54][55]. A recent genome-wide association study on tobacco use revealed a negative genetic correlation for MDD with age at smoking initiation and a positive genetic correlation between MDD and smoking initiation in general as well as cigarettes per day [53].…”
Section: Smoking Behavior Of Psychiatric Patientsmentioning
confidence: 99%
“…Several genetic studies have found that there is a correlation between smoking status and major depressive disorder (MDD) [51][52][53][54][55]. A recent genome-wide association study on tobacco use revealed a negative genetic correlation for MDD with age at smoking initiation and a positive genetic correlation between MDD and smoking initiation in general as well as cigarettes per day [53]. Additionally, smoking contributes to modifications of the oral, lung, and gut microbiome, potentially causing various diseases [56][57][58][59].…”
Section: Smoking Behavior Of Psychiatric Patientsmentioning
confidence: 99%